Analysis of Liposoluble Composition, Antibacterial and Antioxidant Activities of Artemisia argyi in Zhangjiakou - Yongbin XU; Xinmin XIONG; Youduo HE; Jia CUI; Jiangang TUO; Hongyu ZHAO (Shipin gongye ke-ji)
There are rich and high-quality Artemisia argyi resources in Zhangjiakou region. Soxhlet extraction method was used to extract the liposoluble components of Artemisia argyi in Zhangjiakou which could effectively use Artemisia argyi resources to enhance its product value. The main components of liposoluble components of Zhangjiakou Artemisia argyi were analyzed by GC-MS. The antibacterial activity against Gram-negative bacteria and Gram-positive bacteria was determined by filter paper disk test. The scavenging ability of the extracted components on DPPH radical, hydroxyl radical and ABTS+ radical was investigated, and their antioxidant properties were analyzed. The results showed that 41 chemical components were detected in the liposoluble components of Zhangjiakou Artemisia argyi. The main types of compounds were aliphatic alcohols, esters, ketones, acids and aromatic compounds. There were 11 components with relative content greater than 1%, of which 4-C-methyl-myo-linositol comparative content was as high as 66.65%. The liposoluble components of Zhangjiakou Artemisia argyi had certain inhibitory effects on Escherichia coli and Staphylococcus aureus. The minimum inhibitory concentrations of Staphylococcus aureus and Escherichia coli were 4.69 and 9.38 μL/mL. The liposoluble components of Zhangjiakou Artemisia argyi had significant scavenging effects on DPPH radical, hydroxyl radical and ABTS+ radical, and the IC50 was 12.85, 6.32 and 4.17 μL/mL. The results confirmed that the liposoluble components of Zhangjiakou Artemisia argyi had good antibacterial and antioxidant activities.